Hubungan primigravida dan umur dengan kejadian preeklamsia/eklamsia pada ibu bersalin - Fatimah Fatimah; Margono Margono; Nining Wiyati (Jurnal Kesehatan Ibu dan Anak, 2013)
Based on SDKl 2007 maternal mortality rate are 228 per 100.000 live births. ln east Kalimantan at 2010 maternal mortality are 90 case, one of death caused by pre-eclampsia/eclampsia. on 2011, from 923 women in labor in Panglima Sebaya General Hospital there are 307 had pre-eclampsia/eclampsia. Pre-eclampsia/eclampsia influenced by several risk factors such as primigravidarum and ages. Purpose of this study is to know correlation of primigravidarum and ages with pre-eclampsia/eclampsia on women in labor in Panglima Sebaya General Hospital. This study used observational analytic with cross sectional design. Sampling methods used purposive sampling, the number of samples are 340 case. Data analysis used SPSS for Windows Release 16.0 program. Bivariate analysis used chi-square test and multivariate analysis used regression logistic test. The result of study: chi--square test for primigravidarum have p-value (0.002) <0.05 and Rasio Prevalence (RP)=1.988(95% CI 1.296-3.079), variable of age p-value(0.000)< 0.05, RP=2.662 (95% CI 1.656-4.116) and for regression logistic test for variable of primigravida the result is p-value(0.003) < 0.05 and coefficients regression 0.665, variable of ages have p-value(0.000) < 0.05, coefficients regression 0.938, and R square 0,99.